EFFECT OF NINE SQUARES TRAINING WITH MUSIC ON BALANCE AND AGILITY OF CHILDREN WITH SPECIAL NEEDS: INTEGRATION LEARNING - Youyen, Montean (Academic Journal of Thailand National Sports University, 2022)
EFFECT OF NINE SQUARES TRAINING WITH MUSIC ON BALANCE AND AGILITY OF CHILDREN WITH SPECIAL NEEDS: INTEGRATION LEARNING Montean Youyen Health Division Department, Faculty of Education, Ramkhamhaeng University ABSTRACT This research aimed to study and compare effects of nine squares training with music on balance and agility of children with special needs by using integration learning. Participants were six students of the Demonstration of Ramkhamhaeng University with special needs studying in secondary education, first semester, Year 2019, aged between 12-15 years old consisted of 1) students with special needs, and 2) student with multiple disability including physical and speech, using purposive sampling. This research took eight weeks, designed to train a nine squares with music, three days a week, 30 min a time as Monday, Wednesday, and Friday, between 03.30-04.00 pm., 12 hours in total. Research tools were 1) The Stork Stand Test, 2) the Agility T-Test, 3) the Nine Squares Training, and 4) six rhythm background music. The statistic used for analyze the data were median, quartile (Q), quartile deviation (Q.D.), and statistic used for examine hypothesis was the Wilcoxon Signed Ranks Test and the social science program. Results were: Median and Quartile Deviation of the balance before training was 8.62,1.51, and after training at Week 4, 6, 8 were 9.58, 1.76; 13.39, 1.91; 20.03, 2.28, respectively. Median and Quartile Deviation of agility before training was 26.62, 2.73, and after training at Week 4, 6, 8 were 21.20, 2.48; 19.68, 2.19; 18.62, 1.23, respectively. Balance and Agility before and after training a nine squares with music in special needs children by using integration learning had high balance and agility abilities after 8-week training than before training, as a statistical significant of Alpha level at the 0.05. Keywords: Nine squares training, music, balance, agility, children with special needs, integration learning